Dynamic processes determine precipitation variability in Eastern Central Europe since the Last Glacial Maximum - Warken, Sophie F.; Riechelmann, Dana F. C.; Fohlmeister, Jens; Schröder-Ritzrau, Andrea; Frank, Norbert; Scholz, Denis; Jochum, Klaus P.; Mirea, Ionuț-Cornel; Constantin, Silviu; Spötl, Christoph (Communications earth & environment, 2024)
The response of European precipitation variability to climate change is still poorly understood. Here we present a high-resolution speleothem record of Eastern Central European (ECE) autumn/winter precipitation to study decadal to centennial hydroclimatic variations in the European-Atlantic sector since the Last Glacial Maximum. The Cloşani Cave δ18O record shows that the reorganization of the North Atlantic jet following the demise of the Northern Hemispheric ice sheets lasted until c. 6000 to 5000 years before present. Trace element-derived semi-quantitative autumn/winter precipitation amount reveals that the late Glacial and the early to mid-Holocene experienced about 20-30% higher precipitation than present. During the deglaciation, we detect an increased decadal to centennial precipitation variability decoupled from millennial-scale North Atlantic temperature changes. The findings suggest that dynamic (rather than thermodynamic) processes determine regional precipitation variability and the probability of extreme precipitation events in ECE, highlighting the importance of understanding such dynamics for future predictions.
Gesehen am 13.01.2025